Linking science with policy: the importance of incorporating clear roles for knowledge brokers into research-for-development organizations - Cramer, Laura (Frontiers in Sustainable Food Systems, 2024)
Agriculture and food systems research and international development work will not proceed at the necessary speed without clear attention to the role of knowledge brokers within science-policy-practice interfaces. For research to be taken up and incorporated in policy frameworks, knowledge brokering is essential. Scaling of research for development findings will happen through other impact pathways as well, such as development of business models with the private sector, but development and implementation of robust and coherent policies informed by credible evidence is necessary for institutionalizing the work of agriculture and food systems research. Such policies are needed at multiple levels, and knowledge brokers are needed at these different levels as well. Examples of the importance of knowledge brokers in agricultural research for development from the livestock sector and its interaction with the climate change arena are used to illustrate this call for more attention to knowledge brokering.